2017
DOI: 10.1371/journal.pone.0174816
|View full text |Cite
|
Sign up to set email alerts
|

Sponge symbioses between Xestospongia deweerdtae and Plakortis spp. are not motivated by shared chemical defense against predators

Abstract: The recently described epizoic sponge-sponge symbioses between Xestospongia deweerdtae and two species of Plakortis present an unusual series of sponge interactions. Sponges from the genus Plakortis are fierce allelopathic competitors, rich in cytotoxic secondary metabolites, and yet X. deweerdtae flourishes as an epizoic encrustation on Plakortis deweerdtaephila and Plakortis symbiotica. Our objective in this study was to evaluate the hypothesis that X. deweerdtae grows epizoic to these two species of Plakort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Correlating the deterrent activity of associated and non-associated sponge specimens indicated that both members of the symbiosis benet from the presence of the other through shared metabolic defensive chemistry, although it is suggested that Plakortis is more chemically defended than Xestospongia and only minimal translocation of metabolites is likely. 519 The production of discodermolide in aquaculture studies of Discodermia dissoluta at two sites in the Colombian Caribbean using xed or suspended culturing showed that production of the target compound was independent of both location and the conditions used, although a negative correlation with temperature was noted. Production of this important bioactive compound ranged from 20-270 mg g À1 of dry sponge.…”
Section: Spongesmentioning
confidence: 99%
“…Correlating the deterrent activity of associated and non-associated sponge specimens indicated that both members of the symbiosis benet from the presence of the other through shared metabolic defensive chemistry, although it is suggested that Plakortis is more chemically defended than Xestospongia and only minimal translocation of metabolites is likely. 519 The production of discodermolide in aquaculture studies of Discodermia dissoluta at two sites in the Colombian Caribbean using xed or suspended culturing showed that production of the target compound was independent of both location and the conditions used, although a negative correlation with temperature was noted. Production of this important bioactive compound ranged from 20-270 mg g À1 of dry sponge.…”
Section: Spongesmentioning
confidence: 99%
“…These compounds were isolated together as an inseparable mixture from the sy otic association of two Caribbean marine sponges, Plakortis symbiotica-Xestosp deweerdtae, collected on Mona Island, off the west coast of Puerto Rico [27]. This sponge consortium, originally classified as an association between Plakortis halichondr and Xetospongia deweerdtae [28,29], has been shown to host molecules with unique ch cal structures and exceptional bioactivities. For example, smenothiazole A, which played a MIC value of 4.1 µg/mL against Mycobacterium tuberculosis [30], along These compounds were isolated together as an inseparable mixture from the symbiotic association of two Caribbean marine sponges, Plakortis symbiotica-Xestospongia deweerdtae, collected on Mona Island, off the west coast of Puerto Rico [27].…”
Section: Introductionmentioning
confidence: 99%
“…Some Xestospongia spp. also form symbiotic relationships with other prokaryotes [ 23 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%